Perfusion culture of Chinese Hamster Ovary cells for bioprocessing applications. (3rd October 2022) - MacDonald, Michael A.; Nöbel, Matthias; Roche Recinos, Dinora; Martínez, Verónica S.; Schulz, Benjamin L.; Howard, Christopher B.; Baker, Kym; Shave, Evan; Lee, Yih Yean; Marcellin, Esteban; Mahler, Stephen; Nielsen, Lars Keld; et al.
Abstract: Much of the biopharmaceutical industry's success over the past 30 years has relied on products derived from Chinese Hamster Ovary (CHO) cell lines. During this time, improvements in mammalian cell cultures have come from cell line development and process optimization suited for large-scale fed-batch processes. Originally developed for high cell densities and sensitive products, perfusion processes have a long history. Driven by high volumetric titers and a small footprint, perfusion-based bioprocess research has regained an interest from academia and industry. The recent pandemic has further highlighted the need for such intensified biomanufacturing options. In this review, we outline the technical history of research in this field as it applies to biologics production in CHO cells. We demonstrate a number of emerging trends in the literature and corroborate these with underlying drivers in the commercial space. From these trends, we speculate that the future of perfusion bioprocesses is bright and that the fields of media optimization, continuous processing, and cell line engineering hold the greatest potential. Aligning in its continuous setup with the demands for Industry 4.0, perfusion biomanufacturing is likely to be a hot topic in the years to come.